Pengaruh Pengungkapan Akuntansi Hijau (Green Accounting) Terhadap Profitabilitas Pada Perusahaan Sektor Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019 – 2021: (Studi Konseptual) - Poeja Pramudianti (AKUNTANSI 45, 2023)
Green Accounting is a corporate disclosure with the aim of transparency of corporate responsibility for environmental sustainability. The purpose of this study is to prove if there is a relationship between green accounting disclosures and profitability. This study uses a research method in the form of a literature review with data on mining companies listed on the IDX for the 2019-2021 period. The results of this study indicate that there is no significant relationship between Green Accounting disclosures and the level of company profitability.